Adsorption Studies for Arsenic Removal Using Activated Moringa oleifera - T. Sumathi; G. Alagumuthu (International Journal of Chemical Engineering, 2014)
A new low cost adsorbent, activated Moringa oleifera has been developed for aqueous arsenic removal. Batch experiments were revealed that As removal was up to 71.3% using activated Moringa oleifera. Kinetics studies revealed that Langmuir isotherm was followed with a better correlation than the Freundlich isotherm. The thermodynamic parameters such as ΔH, ΔS, and ΔG were computed from the experimental data. These values show that the adsorption is endothermic and spontaneous in nature. Thus, this recently developed cost-effective novel biosorbent, activated Moringa oleifera can be used as household level to mitigate the arsenic problem.